Socioeconomic, Psychiatric and Materiality Determinants and Risk of Postpartum Depression in Border City of Ilam, Western Iran - Taherifard, Pegah; Delpisheh, Ali; Shirali, Ramin; Afkhamzadeh, Abdorrahim; Veisani, Yousef (Depression Research and Treatment, 2013)
Background. Postpartum depression (PPD) is considered as one of the mood disturbances occurring during 2-3 months after delivery. The present study aimed to determine the prevalence of PPD and its associated risk factors in border city of Ilam, western Iran. Methods. Through a descriptive cross-sectional study in 2011, overall, 197 women who attended Obstetrics & Gynecology clinics postpartumly in the border city of Ilam, western Iran, were randomly recruited. A standard questionnaire that was completed by a trained midwife through face to face interviews was used for data gathering. Results. Mean age ± standard deviations was 27.9 ± 5.2 years. Prevalence of PPD was estimated to be 34.8% (95% CI: 27.7–41.7). A significant difference was observed among depression scores before and after delivery (P≤0.001). Type of delivery (P=0.044), low socioeconomic status (P=0.011), and women having low educational level (P=0.009) were the most important significant risk factors associated with PPD. The regression analysis showed that employed mothers compared to housekeepers were more at risk for PPD (adjusted OR = 2.01, 95% CI: 1.22–2.28, P=0.003). Conclusions. Prevalence of PPD in western Iran was slightly higher than the corresponding rate from either national or international reports.